(untitled) - Berry, Brian J. L. (Englewood Cliffs, N.J., 1976)
This book introduce about geographic fundamentals, economic fundamentals, theories of location, exchange and interaction, regional economic structure. The world's industrial heartland economies...
Keywords: Địa lý kinh tế,Economic geography